The Role of Budget Planning and Budget Realization in Improving The Effectiveness of Budget Implementation (Study at Padjadjaran University Bandung) - Darmawan Darmawan; Dodi Sukmayana; Annisa Fitri Anggraeni (Greenation Research & Yayasan Global Resarch National, 2023)
Darmawan, 2021, The Role of Budget Planning and Budget Realization in Improving the Effectiveness of Budget Implementation (Study at Padjadjaran University Bandung) This study aims to determine and analyze (1) budget planning and (2) budget realization in improving (3) the effectiveness of budget implementation at Padjadjaran University Bandung for the period 2016-2020 either partially or simultaneously. The research method used in this study is a time series, the unit of analysis in this study is the Annual Activity Plan and Budget of Padjadjaran University Bandung for 2016-2021. This type of quantitative research using descriptive quantitative methods. Data collection techniques were carried out by observation and literature study. Based on the results of the study, it was found that the budget planning at Padjadjaran University for 2016-2020 was good, budget realization at Padjadjaran University for 2016-2020 was generally good, and the effectiveness of budget implementation at Padjadjaran University was also very effective. The role of budget planning and budget realization is able to increase the effectiveness of budget implementation at Padjdjaran University Bandung in 2016-2020 simultaneously and partially. However, partially budget realization dominantly affects the effectiveness of budget implementation rather than budget planning. Because the realization of the dominant budget affects the effectiveness of budget implementation, it becomes the key in increasing the effectiveness of budget implementation. Therefore, Padjadjaran University needs improvements in its budget planning so that the effectiveness of budget implementation is increasing.